The knife that killed me - McGowan, Anthony (London : Definitions, 2008)
Paul Varderman, a secondary student in an English Catholic School, is a loner until, just as he is becoming friends with "the freaks," the school bully encourages Paul to join his gang and gives him a knife to carry as an incentive.
Young Adult.
Young Adult
Keywords: Bullying -- Juvenile fiction; Catholic schools -- Juvenile fiction; Friendship -- Juvenile fiction; Gangs -- Juvenile fiction; Murder -- Juvenile fiction; Schools -- Juvenile fiction; Bullies -- Fiction; Catholic schools -- Fiction; Friendship -- Fiction; Gangs -- Fiction; Murder -- Fiction; Schools -- Fiction; Bullies -- Fiction; Catholic schools -- Fiction; Friendship -- Fiction; Gangs -- Fiction; Homicide -- Fiction; School stories; England -- Juvenile fiction; England -- Fiction; England -- Fiction